Safety and Performance of Narhinel 0.9% Sodium Chloride Monodose and Otrisal 0.74% Sodium Chloride Monodose Nasal Saline Solutions and Nasal Aspirators in Real-World Settings: Postmarket Clinical Follow-up Study Results - Mathieu M. Albasser, PhD, MSc, BSc; Edwin Sanchez, MSc, BA; Mariane B． Fernandes, PhD, BPharm; Nisha Patel, BSc, MSc; Petr Novak, MUDr, MBA; Martina Hagen, PhD, MS (Elsevier, 2023)
ABSTRACT: Background: Blocked or stuffy nose is a common and bothersome symptom of colds, particularly for young children who are unable to clear their noses on their own. Nasal saline solutions and nasal aspirators are designed to gently cleanse and remove blocking nasal secretions. Objective: To assess the safety and performance of 2 monodose isotonic saline solutions (Narhinel 0.9% and Otrisal 0.74% sodium chloride; GSK Consumer Healthcare SARL, a Haleon company, Nyon, Switzerland) and 2 nasal aspirators with disposable hard- and soft-nozzle refills used as a standalone or combination treatment. Methods: We conducted 2 observational, online questionnaire-based, postmarket clinical follow-up studies in Europeans who had used any of the devices ≥1 time in the past 6 months. Coprimary objectives were to confirm the safety and performance of the saline solutions (Narhinel and Otrisal, Study 1) and nasal aspirators (with hard- and soft-nozzle refills, Study 2). Safety was assessed via the proportion of patients reporting adverse events and/or device malfunctions while using the devices within the previous 6 months, and performance was assessed by satisfaction rated on a 5-point scale, with "satisfied" and "very satisfied" being the highest performance ratings. Results: A total of 1136 (Study 1) and 1237 (Study 2) questionnaires were initiated by volunteer participants. Less than 2% of participants reported adverse events for any evaluated product in the previous 6 months. Most participants were "satisfied" or "very satisfied" with the devices for their intended use, with 78% to 91% of participants in the Narhinel arm, 73%-94% in the Otrisal arm, 71% to 95% in the soft-nozzle arm, and 71% to 80% in the hard-nozzle arm giving these ratings. Conclusions: These data support the safety and performance of 2 monodose saline solutions (Narhinel and Otrisal) for nasal cleansing, nasal moisturization, and/or loosening nasal secretions, and of nasal aspirators (with hard- and soft-nozzle refills) for clearing a blocked nose and removing nasal secretions.